Rerum Novarum: Um guia de leitura - Júnior, Francisco de Aquino (Revista eclesiástica brasileira, 2019)
The Encyclical Rerum Novarum is extremely important for the dialogue between the Church and the modern world, and, in particular for the practical-theoretical development of the social dimension of the faith. It is a decisive text in the process of ecclesial renovation that had as result the Vatican II Council and the reception it had in Latin America. However, it is not a text as simple and easy to understand as it may seem at first sight. Hence the importance of this work that, as indicated by its subheading, intends to be a reading guide for the Encyclical. It begins by pointing to the socio-ecclesial context in which the Encyclical appears and to which it intends to be an answer. It gives a panoramic presentation of its basic structure and contents. And it concludes by emphasizing some important points for its adequate comprehension and interpretation.